Global implementation research capacity building to address cardiovascular disease: An assessment of efforts in eight countries. - Mary Beth Weber; Ana A Baumann; Ashlin Rakhra; Constantine Akwanalo; Kezia Gladys Amaning Adjei; Josephine Andesia; Kingsley Apusiga; Duc A Ha; Mina C Hosseinipour; Adamson S Muula; Hoa L Nguyen; LeShawndra N Price; et al. (Public Library of Science (PLoS), 2023)
Cardiovascular diseases are the leading causes of morbidity and mortality worldwide, but implementation of evidence-based interventions for risk factors such as hypertension is lacking, particularly in low and middle income countries (LMICs). Building implementation research capacity in LMICs is required to overcome this gap. Members of the Global Research on Implementation and Translation Science (GRIT) Consortium have been collaborating in recent years to establish a research and training infrastructure in dissemination and implementation to improve hypertension care. GRIT includes projects in Ghana, Guatemala, India, Kenya, Malawi, Nepal, Rwanda, and Vietnam. We collected data from each site on capacity building activities using the Potter and Brough (2004) model, mapping formal and informal activities to develop (a) structures, systems and roles, (b) staff and infrastructure, (c) skills, and (d) tools. We captured information about sites' needs assessments and metrics plus program adaptations due to the COVID-19 pandemic. All sites reported capacity building activities in each layer of the Capacity Pyramid, with the largest number of activities in the Skills and Tools categories, the more technical and easier to implement categories. All sites included formal and informal training to build Skills. All sites included a baseline needs assessment to guide capacity building activities or assess context and inform intervention design. Sites implementing evidence-based hypertension interventions used common implementation science frameworks to evaluate implementation outcomes. Although the COVID-19 pandemic affected timelines and in-person events, all projects were able to pivot and carry out planned activities. Although variability in the activities and methods used existed, GRIT programs used needs assessments to guide locally appropriate design and implementation of capacity building activities. COVID-19 related changes were necessary, but strong collaborations and relationships with health ministries were maintained. The GRIT Consortium is a model for planning capacity building in LMICs.